2017
DOI: 10.1186/s41610-017-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal community composition across the soil depth profiles in a fallow field

Abstract: Background: Soil microorganisms play key roles in nutrient cycling and are distributed throughout the soil profile. Currently, there is little information about the characteristics of the microbial communities along the soil depth because most studies focus on microorganisms inhabiting the soil surface. To better understand the functions and composition of microbial communities and the biogeochemical factors that shape them at different soil depths, we analyzed microbial activities and bacterial and fungal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
33
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 28 publications
10
33
2
1
Order By: Relevance
“…We did not observe differences in diversity indices or species richness with depth. Similar lack of change in fungal diversity and community composition with depth has been described in fallow fields dominated by Ascomycetes (Ko et al, 2017), although several other studies have observed decreasing richness and diversity with increasing soil depth (Rahman et al, 2008;Degrune et al, 2016;Schlatter et al, 2018). The observed increase in relative abundance of AMF and undefined saprotrophs below 5 cm in the no-till treatments may have been due to specific taxa within these groups showing greater sensitivity to daily temperature swings, wet-dry cycles or other environmental effects that are more pronounced near soil surface.…”
Section: Depth Effectssupporting
confidence: 76%
“…We did not observe differences in diversity indices or species richness with depth. Similar lack of change in fungal diversity and community composition with depth has been described in fallow fields dominated by Ascomycetes (Ko et al, 2017), although several other studies have observed decreasing richness and diversity with increasing soil depth (Rahman et al, 2008;Degrune et al, 2016;Schlatter et al, 2018). The observed increase in relative abundance of AMF and undefined saprotrophs below 5 cm in the no-till treatments may have been due to specific taxa within these groups showing greater sensitivity to daily temperature swings, wet-dry cycles or other environmental effects that are more pronounced near soil surface.…”
Section: Depth Effectssupporting
confidence: 76%
“…Moreover, our results showed that the relative abundance of Ascomycota gradually decreased with the downward movement of root depths (Fig. 2b), which was consistent with the results of Ko, Daegeun et al [54]. On this basis, we found that the relative abundance of Ascomycota in Glycyrrhiza in ata had a signi cant difference at different root depth, but Glycyrrhiza uralensis and Glycyrrhiza glabra were not signi cant difference, indicating that some endophytes may preferentially proliferate in a certain ecological region and play different ecological roles from other endophytes.…”
Section: Discussionsupporting
confidence: 92%
“…Though the overall Proteobacteria were more abundant in 5–15 cm soils, the class Betaproteobacteria was most abundant in 0–5 cm, which was also found in other study [70]. Similar to our results, others have also reported that Chloroflexi [67, 68] and Nitrospirae [71] increase in abundance with soil depth.…”
Section: Discussionsupporting
confidence: 91%